Basic income : the material conditions of freedom - Raventós, Daniel (Pluto Press, 2007)
Basic Income is a policy idea that could help us revolutionise the way we organise society. This book is the first proper guide to basic income -- what it is, how we can organise it, and how it can benefit the majority in different spheres of their lives. Basic Income is simply the idea that everyone in a given society has a right to a minimal income. This is paid by the state out of taxation. Set at a subsistence level, it would take the place of unemployment and other benefits. This would bring profound social changes. Anyone could opt out of employment at any time. Those with few skills would no longer be forced to take up jobs with poor prospects, and employers offering McJobs would be forced to offer better terms. And money wasted by the state in means testing and tracing benefit fraud is saved The campaign in favour of basic income is growing and governments are beginning to take notice. This is a clear, concise guide to the principles and practicalities of this revolutionary idea.